HUBUNGAN SIKAP KERJA DAN KARAKTERISTIK INDIVIDU DENGAN GEJALA CUMULATIVE TRAUMA DISORDERS (CTDs) PADA PEKERJA BAGIAN PENCETAKAN KULIT LUMPIA DI KELURAHAN KRANGGAN SEMARANG TENGAH - Putri Desriani; Siswi Jayanti; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2017)
Cumulative Trauma Disorders (CTDs) are disorders of the soft tissues of the body which include muscles, tendons, ligaments, nerves and blood vessels due to work demands that exceed the limits of the body's physical ability. Work posture and individual characteristics can be risk factors for CTDs symptoms at maker lumpia leathers. The aim of this study was to analyze the association of work posture and individual characteristics with the symptoms of cumulative trauma disorders among workers of lumpia leathers maker. This type of research is explanatory research with cross sectional approach. Population of this research is workers of lumpia leathers maker totaling 30 peoples. The sample in this study were drawn from total population. The symptoms of CTDs was measured subjectively using Nordic Body Map. Statistical analysis is using Chi Square correlation test. The results showed there are no correlation between work posture with symptoms of CTDs at neck (sig = 0,301), back (sig = 0,584), upper arm (sig = 0,528), lower arm (sig = 493), wrist (sig = 0,842) and leg (sig = 0,552). There is a correlation between age with symptoms of CTDs at neck (sig = 0,037), working period with symptoms of CTDs at back (sig = 0,001), duration of work with symptoms of CTDs at upper arm (sig = 0,00) and duration of work with symptoms of CTDs at leg (sig = 0,002). Business owner should improves work tools to conform to ergonomic standards and workers should doing stretch before starting the job.